1992
DOI: 10.1111/j.1600-0765.1992.tb01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell leukocyte adhesion molecule‐1 (ELAM‐1) and intercellular adhesion molecule‐1 (ICAM‐1) expression in gingival tissue during health and experimentally‐induced gingivitis

Abstract: The changes in vascular adhesion molecule expression and numbers of infiltrating leukocytes during a 21-day experimental gingivitis episode were investigated immunohistochemically. Monoclonal antibodies to ELAM-1 (1.2B6), ICAM-1 (6.5B5), CD3 (OKT3-pan-T cell) and neutrophils (PMN-elastase) were used to identify positive vessels and leukocytes within gingival biopsies taken on d 0, 7, 14 and 21. Vascular endothelium expressed ELAM-1 and ICAM-1 both in clinically 'healthy' tissue (d 0) and in experimentally infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 34 publications
6
96
0
1
Order By: Relevance
“…The viability of cells treated in combination with sodium bicarbonate was improved significantly compared to cells treated with butyric acid alone; sodium bicarbonate alone had no effect on ICAM-1 expression. ICAM-1 expression in the epithelium is thought to play an important role in leukocyte transendothelial migration to areas of inflammation in gingival tissue (16)(17)(18). Our results indicated that sodium bicarbonate significantly Fig.…”
Section: Discussionsupporting
confidence: 66%
“…The viability of cells treated in combination with sodium bicarbonate was improved significantly compared to cells treated with butyric acid alone; sodium bicarbonate alone had no effect on ICAM-1 expression. ICAM-1 expression in the epithelium is thought to play an important role in leukocyte transendothelial migration to areas of inflammation in gingival tissue (16)(17)(18). Our results indicated that sodium bicarbonate significantly Fig.…”
Section: Discussionsupporting
confidence: 66%
“…For example, in the setting of chronic inflammation, ELAM-I is preferentially expressed on venules in the skin (Norris et al, 1991). Expression of ELAM-I's lymphocyte ligand, cutaneous lymphocyte-associated antigen (CLA), is largely limited to a skin-homing subset of memory/effector T-lymphocytes (Berg et al, 1991 (Moughal et al, 1992;Tonetti et al, 1994 sented by a cell that takes up and degrades it and displays the relevant immunogenic fragments in the context of MHC Class 11 products An antigen-presenting cell (APC) therefore must express MHC Class 11 antigens. It has been speculated that normally MHC Class 11 antigennegative cell types-including endothelial cells (De Waal et ci., 1983, Geppert andLipsky, 1985), astrocytes (Wong et ci., 1984), keratinocytes (Breathnach and Katz, 1983;Basham et cil., 1984), and fibroblasts (Pober et al, 1983;Geppertand Lipsky, 1985, Maureretal., 1985, 1987 Previous studies systematically examined APC function of MHC Class II-positive dermal fibroblasts which had been stimulated with IFN-y (Pober et cil, 1983, Geppert and Lipsky, 1985, Umetsu et al, 1985Maurer et cal., 1987).…”
Section: (3) Interaction With Endothelial Cellsmentioning
confidence: 99%
“…ICAM1, which is a widely expressed cell adhesion molecule [48][49][50] and belongs to the immunoglobulin super family, plays an important physiological role in routing polymorphonuclear neutrophils to the gingival sulcus efficiently and initiating a host response toward the implant. The expression of endothelial cell adhesion molecules (CAMs) for leukocytes, P-selectin, E-selectin, and ICAM1 is significantly upregulated in inflamed tissues by FGF2.…”
mentioning
confidence: 99%